Leveraging Education Report Technology for Data-Driven School Planning and Teacher Performance - Litasari, Rini; Herawati, Endang Sri Budi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Education Report Technology has emerged as a strategic digital platform for supporting data-driven school planning, strengthening instructional decision-making, and enhancing teacher performance within evidence-based educational management. This study aims to synthesize current evidence regarding how Education Report Technology contributes to school planning and teacher performance through the implementation of Data-Driven Decision Making (DDDM). A Systematic Literature Review (SLR) was conducted following the PRISMA framework. One hundred articles indexed in Scopus and other relevant databases were initially identified, with ten studies meeting the predefined inclusion criteria for in-depth thematic synthesis. The analysis generated four major themes. First, digital data literacy and principals’ managerial competence are essential for transforming educational data into meaningful planning and instructional improvement. Second, Education Report Technology, including digital dashboards and Education Management Information Systems (EMIS), supports evidence-based school planning and contributes to teacher performance, although its effectiveness varies according to institutional readiness. Third, implementation is constrained by inadequate digital infrastructure, limited data literacy, and weak data-driven organizational culture. Fourth, effective interventions include data literacy training, technology-supported teacher appraisal systems based on the Balanced Scorecard (BSC) and PDCA framework, and collaborative data dialogue supported by digital platforms. The findings indicate that Education Report Technology functions not merely as an administrative reporting tool but as an educational technology ecosystem that facilitates continuous school improvement, teacher professional growth, and evidence-informed instructional practices. These findings provide practical implications for policymakers, school leaders, and teachers seeking to optimize digital technologies for sustainable educational quality improvement.